Targeting the Microenvironment in MDS: The Final Frontier - Teodorescu, Patric; Pasca, Sergiu; Dima, Delia; Tomuleasa, Ciprian; Ghiaur, Gabriel (Frontiers in Pharmacology, 2020)
Myelodysplastic syndromes are a heterogeneous group of malignant disorders of hematopoietic stem and progenitor cells, mainly characterized by ineffective hematopoiesis leading to peripheral cytopenias and progressive bone marrow failure. While clonal dominance is nearly universal at diagnosis, most genetic mutations identified in patients with MDS do not provide a conspicuous advantage to the malignant cells. In this context, malignant cells alter their adjacent bone marrow microenvironment and rely on cell extrinsic factors to maintain clonal dominance. The profoundly disturbed BME favors the myelodysplastic cells and, most importantly is detrimental to normal hematopoietic cells. Thus, the myelodysplastic microenvironment not only contributes to the observed cytopenias seen in these patients but could also negatively impact the engraftment of normal, allogeneic hematopoietic cells in patients with myelodysplastic syndromes that undergo bone marrow transplant. Therefore, successful therapies in myelodysplastic syndromes should not only target the malignant cells but also reprogram their bone marrow microenvironment. Here, we will provide a synopsis of how drugs currently used or on the verge of being approved for the treatment of MDS may achieve this goal.